Philosophical and Theological Attitudes to Spirituality - Verbylaitė, Dalia (Acta Paedagogica Vilnensia, 2003)
There is a contradiction between spiritual life and economical, technical welfare which breaks harmony and peace in people’s life. It is important today to understand the authentic spirituality, to look at the roots and depth of spirituality, where spirituality is, what is an object of spirituality, and how spirituality changes people’s life. The uniqueness of spirituality is that spirituality is concerned for all human reality. That’s why contemporary spirituality is an object of all human experience and it is an interdisciplinary matter. The purpose of this article is to present t Christian philosophical understanding of spirituality. The article consists of two sections: first, to present spiritual human forms and second, to evaluate various philosophical attitudes for Christian spiritual education. Methods: analysing, comparing, and evaluating of scientific philosophical and theological literature. The analysis of the scientific literature reveals that human spirituality allows to make following conclusions. 1) Human spirituality can be defined as an ability to unite oneself with transcendence (God) and to make a relationship with it. 2) Human spirituality through relation person-person is the one to realize a true human existence which opens the way to the highest values and existence of Other (God). 3) Human spirituality manifests itself as relation with oneself, with other (God. people, creation, and cosmos). Second part of this article analyses philosophical tendencies that are important to Christian spiritual education. The conclusions are following. 1) Idealistic human vision is to become more human, what helps people to become more perfect, divine. 2) Rationalistic neo-Thomistic vision promote divine and human relationship what is the basics for the right relations among people. 3) Realistic view promote human experience as the first and the main one in the process of understanding. 4) Existentialism and phenomenalism penetrates human being, his manifestations. It helps to find meaning in various situations and experiences of life. 5) Humanism and personalism seeks realization of a personality which is essential moment in spiritual education.